Linguocultural Features of Symbol and Metaphor - Sharipova Dilnoza Shavkatovna; Qutliyeva Muhayyo G’ulomovna (International Journal on Integrated Education, 2021)
The article discusses the features of a symbol that distinguish it from a metaphor. The article gives a brief overview of the formation and stages of development of symbols of cultural unity, their role in society, analyzes some semantic, structural and functional features, reveals the connection of symbols with one of the related phenomena - metaphors. In the presence of an essential opposition of a symbol to a metaphor as a sign to a path, as a result of their use, these phenomena lead to an expanded view of the nature of things. In Western philosophy, special attention is paid to this issue, and a large number of scientific and theoretical ideas are expressed on it. However, this extension is of a different nature, which contrasts the symbol with the metaphor in a number of functional parameters, and the operation with the metaphor and the symbol presupposes various mental procedures within the framework of speech (metaphor), cultural and linguistic (symbol) competencies.